2019
DOI: 10.1212/wnl.0000000000007574
|View full text |Cite
|
Sign up to set email alerts
|

ApoB, small-dense LDL-C, Lp(a), LpPLA 2 activity, and cognitive change

Abstract: ObjectiveTo examine the association of specific lipoproteins/inflammatory enzyme with cognitive change.MethodsWe examined the association of apolipoprotein B (ApoB), small-dense low-density lipoprotein cholesterol (sdLDL-C), lipoprotein (a) (Lp[a]), and lipoprotein-associated phospholipase A2 (LpPLA2) activity with 15-year change in Delayed Word Recall Test, Digit Symbol Substitution Test (DSST), Word Fluency Test (WFT), and overall summary score in 9,350 participants in the Atherosclerosis Risk in Communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Individual scores were converted to z‐scores using Visit 2 means and standard deviations as referents. We calculated a global measure of cognition for each participant from the individual z‐scores, which was then converted to a global z‐score using Visit 2 mean and standard deviation as referents 19,20,23,24 …”
Section: Methodsmentioning
confidence: 99%
“…Individual scores were converted to z‐scores using Visit 2 means and standard deviations as referents. We calculated a global measure of cognition for each participant from the individual z‐scores, which was then converted to a global z‐score using Visit 2 mean and standard deviation as referents 19,20,23,24 …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, two other studies observed that for every 10 mg increase in small-dense low-density lipoprotein cholesterol (sdLDL-C), there was an accelerated cognitive deterioration. 46 A high concentration of total cholesterol and LDL-C in late life was associated with a rapid cognitive impairment. On the contrary, another study found that MCI patients had a significant amount of small HDL when compared to the Alzheimer group, 47 higher midlife HDL-C halve the risk of developing MCI and lowered risk of dementia later in life, 48 suggesting an association between HDL subclasses and MCI.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a prospective cohort of 2,532 subjects of Finnish ( 15 ) male population in 24.9 years' follow-up, showed that Lp(a) was protective of future dementia risk. Another large prospective cohort study based on four United States communities ( 13 ) showed that higher Lp(a) levels were associated with slower cognitive decline in semantic fluency over 15 years. What is more, negative results were also obtained in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between serum Lp(a) and cognitive impairment or dementia is still controversial. Previous studies have shown that Lp(a) had an adverse effect ( 8 , 9 ) or no effect ( 10 12 ) on cognition, whereas, in recent years some studies have found that it had a beneficial influence ( 13 15 ).…”
Section: Introductionmentioning
confidence: 98%